2016
DOI: 10.2993/0278-0771-36.3.571
|View full text |Cite
|
Sign up to set email alerts
|

Wood Charcoal From Archaeological Sites in the Qinghai Lake Basin, Western China: Implications For Human Resource Use and Anthropogenic Environmental Change

Abstract: The archaeological record of the Qinghai Lake Basin, northeast Tibetan Plateau, western China, contains charcoal-based evidence of significant changes in the distribution of local shrub land and woodland through the last 12,500 14C yr BP. These vegetation trends correspond with regional changes in hunter-gatherer settlement and patterns of Holocene climate change. This charcoal-based record is useful to address current issues concerning the timing of anthropogenic vs. climatic factors in the development of gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…Recently, charcoal records from a Qinghai Lake transect (Kaiser et al, 2007) and from archaeological sites (Rhode, 2016) in Qinghai Lake basin also confirmed that spruce woodland expanded after ~9500 yr BP and grew widely until at least ~4000 yr BP.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Recently, charcoal records from a Qinghai Lake transect (Kaiser et al, 2007) and from archaeological sites (Rhode, 2016) in Qinghai Lake basin also confirmed that spruce woodland expanded after ~9500 yr BP and grew widely until at least ~4000 yr BP.…”
Section: Discussionmentioning
confidence: 88%
“…According to the direct ages of spruce debris or cones, the age of the last living spruce trees in the basin was ~4243±143 cal yr BP (SDT section). An archaeological site (CDH) dated to ~2890±70 yr BP (3037±188 cal yr BP), located on the northern margin of Hudong Sandy Land, also contained a small amount of spruce charcoal (Rhode, 2016). However, the CDH site was dated using seeds of domesticated barley ( Hordeum vulgare ) (Chen et al, 2015), which were significantly younger than the radiocarbon ages of the wood charcoal (Dong et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations